Biodegradation of diesel by local isolate Bacillus pumilus strain NHK - Kaida, Nurulhuda (2012)
Petroleum hydrocarbon such as diesel has become one of the potential sources of environmental contamination in Malaysia. The abundance of diesel in coastal areas and soils cause massive pollution and must be eliminated due to their high toxicity effects. Therefore, this study is about the use of microorganism to alleviate diesel pollution as an alternative technology of chemical- or physical-based oil-pollution treatments. Biodegradation of diesel requires a diesel-tolerant microbe to reduce degradation time. Local bacteria isolated from oil-contaminated soil and water from various locations in Malaysia were screened for their ability to degrade large amount of diesel in a shorter time. Enrichment culture from soil samples gave several isolates capable of degrading diesel. By using gravimetric method, Isolate T5 was selected for further studies because it has been shown to have high diesel-degradation ability in a shorter period and able to use diesel as its carbon and energy source in contrast to the other isolates. The isolate was identified as Bacillus pumilus Strain NHK (1439 bp) (99% sequence homology) by using 16S rRNA molecular phylogenetic analysis. In this study, the isolate exhibite optimum diesel degradation and growth in media containing 5% (v/v) diesel concentration at 30 °C, 0.9% (w/v) of sodium nitrate (NaNO3) as an additional nitrogen source, optimum pH 7.5 (phosphate buffer) and in the presence of 0.01% (v/v) Tween 80 as a surfactant. Gravimetric method revealed that Isolate T5 has been proven to show high diesel-degradation ability and almost 75% of diesel was degraded by Isolate T5 in 20 days as further proven when analyzed using gas chromatography-flame ionization detector (GC-FID). After just 4 days of diesel degradation studies, the biodegradation efficiency rate has significantly increased from 26.7 to 37% with a total increment of 10.3% after growth optimization. The effects of various heavy metal and salinity on diesel degradation were tested in this experiment. The presence of zinc at 5 ppm enhanced diesel degradation by about 18% as compared to control sample while the other heavy metal caused minor inhibition on the diesel degradation and growth of Isolate T5 after 4 days. The best concentration of sodium chloride (NaCI) for diesel degradation was 0 to 4% (w/v). Isolate T5 was then immobilized on gellan gum with the optimum immobilization parameters of 0.75% (w/v), bead’s size of 3 mm diameter and bead number of 30 per 10 ml medium. Diesel degradation was compared between free cells and gellan gum immobilized cells. From the results obtained, at diesel concentration of 5% (v/v), gellan gum immobilized cells degraded diesel oil faster with 96% degradation compared to 83.6% degradation for free cells in 10 days of incubation. The bacterium's characteristics meet the requirements for bioremediation of diesel accidents and pollutions either in soil or coastal area co-contaminated with heavy metals in the tropics. The outcome of this study will contribute towards the knowledge in diesel degradation process in order to support environmental sustainability as well as minimizing costs if conventional technology was used especially for a developing country like Malaysia.